Предмет: Алгебра,
автор: вовик1503
log3(2-x^2) - log3(-x) = 0
Ответы
Автор ответа:
0
log3(2-x²/-x)=0
2-x²/-x=3^0
2-x²/-x=1
2-x²=-x
2-x²+x=0
-x²+x+2=0
x²-x-2=0
D=1-4*1*(-2)=1+8=9
√D=3
x1=1+3/2=2 не подходит. см.проверку
x2=1-3/2=-1
проверка
log3(2-4)-log3(-2)=0 (log не может быть отрицательным)
log3(2+1)-log3(1)=0
2-x²/-x=3^0
2-x²/-x=1
2-x²=-x
2-x²+x=0
-x²+x+2=0
x²-x-2=0
D=1-4*1*(-2)=1+8=9
√D=3
x1=1+3/2=2 не подходит. см.проверку
x2=1-3/2=-1
проверка
log3(2-4)-log3(-2)=0 (log не может быть отрицательным)
log3(2+1)-log3(1)=0
Похожие вопросы
Предмет: Алгебра,
автор: yarinka0809
Предмет: Математика,
автор: Аноним
Предмет: История,
автор: alenchek2404
Предмет: Математика,
автор: лаура1998